Orange Peel-Mediated Green Synthesis of ZnO and CuO Nanoparticles: Evaluation for Antimicrobial Activity and Biocompatibility in Tissue Engineering - Rădulescu, Denisa Maria; Neacșu, Ionela Andreea; Vasile, Bogdan Ștefan; Surdu, Vasile Adrian; Oprea, Ovidiu Cristian; Trușcă, Roxana Doina; Chircov, Cristina; Popescu, Roxana Cristina; Ilie, Cornelia Ioana; Dițu, Lia Mara; Drumea, Veronica; Andronescu, Ecaterina (MDPI, 2025)
The production of green nanomaterials has drawn considerable interest lately in the fields of tissue engineering and biomedicine. Thus, the environmentally friendly synthesis of ZnO and CuO nanoparticles (NPs) utilizing orange peel extract as a natural capping and reducing agent is the main focus of this study. Our comprehensive approach allows for a direct and systematic comparison of physicochemical attributes, biocompatibility, and antimicrobial activity under identical experimental circumstances, in contrast to other research that looked at individual nanoparticles under different conditions. The produced nanoparticles were characterized by techniques such as FTIR, XRD, SEM, TGA, and zeta potential assessment. MG-63 osteoblast-like cells, primary human dermal fibroblast BJ cells, and murine fibroblast L929 cells were used to evaluate biocompatibility using the MTT assay. The results showed dose-dependent cytotoxicity, especially above 25 µg/mL. Furthermore, both qualitative (growth inhibition zone diameter) and quantitative (minimum inhibitory concentration, MIC) techniques were used to assess the antimicrobial efficacy against Candida albicans and Gram-positive and Gram-negative bacteria. According to the obtained results, ZnO NPs showed broad-spectrum efficacy, whereas CuO NPs showed excellent antibacterial activity against Gram-positive bacteria (e.g., S. aureus, MIC = 0.313 μg/μL). The study highlights the potential of green-synthesized nanoparticles for utilization in biomedical applications, and it stresses the need for additional mechanistic research, including ROS measurement, to completely understand how they work.
Keywords: green synthesis; nanoparticles; tissue engineering; copper oxide nanoparticles; zinc oxide nanoparticles; antimicrobial activity; biocompatibility; biofilm inhibition